2013
DOI: 10.1111/jmft.12018
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult Romantic Couples’ Conflict Resolution and Satisfaction Varies with Partner's Attention–Deficit/Hyperactivity Disorder Type

Abstract: Attention-deficit/hyperactivity disorder (ADHD) has previously been associated with less satisfaction and success in romantic relationships. This study compares conflict resolution and problem-solving behaviors in young adult romantic couples either having one partner with ADHD combined type (C-couples), having one partner identified with ADHD inattentive type (IA-couples), or in which neither partner has an ADHD diagnosis (nondiagnosed [ND] couples). Self-reports of current and childhood ADHD symptoms corrobo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 73 publications
(102 reference statements)
2
29
0
Order By: Relevance
“…While preliminary, this is one of a small group of studies to find positive effects of treatment in a core domain of functional impairment for individuals with elevated ADHD symptoms (for others, see Barkley & Cox, 2007;Rostain & Ramsay, 2006;Weiss et al, 2012). Acknowledging the deleterious impact of ADHD symptoms on adult romantic relationships (e.g., Biederman et al, 2006;Canu, Tabor, Michael, Bazzini, & Elmore, 2014;Kessler et al, 2006;Wymbs et al, 2012), finding effects of the integrative group program on romantic relationships is encouraging. Improvement in relationship functioning may be valuable because it could facilitate romantic partners continuing to compensate for the difficulties of adults with elevated ADHD symptoms (Eakin et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…While preliminary, this is one of a small group of studies to find positive effects of treatment in a core domain of functional impairment for individuals with elevated ADHD symptoms (for others, see Barkley & Cox, 2007;Rostain & Ramsay, 2006;Weiss et al, 2012). Acknowledging the deleterious impact of ADHD symptoms on adult romantic relationships (e.g., Biederman et al, 2006;Canu, Tabor, Michael, Bazzini, & Elmore, 2014;Kessler et al, 2006;Wymbs et al, 2012), finding effects of the integrative group program on romantic relationships is encouraging. Improvement in relationship functioning may be valuable because it could facilitate romantic partners continuing to compensate for the difficulties of adults with elevated ADHD symptoms (Eakin et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Individuals with externalizing disorders are more likely to engage in RSB compared to individuals without an externalizing disorder (Flory et al, 2006). However, several studies have also reported romantic relationship impairments among young adults with externalizing disorders (Canu & Carlson, 2007;Canu & Carlson, 2003;Canu, Tabor, Michael, Bazzini, & Elmore, 2014), which is not surprising given the well-documented social impairments among these individuals (Sibley, Evans, & Serpell, 2010). Specifically, young adults with ADHD are viewed as less desirable by confederates compared to young adults without ADHD (Canu & Carlson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, our results may have occurred because the majority of our criterion variables assess positive friendship features (e.g., quantity of friends, connection, and support). Emerging adults with ADHD-C and ADHD-I may equally lack positive interactions, and the subtypes may be better distinguished by the presence of negative interactions in the ADHD-C but not the ADHD-I subtype (Canu et al, 2014). …”
Section: Discussionmentioning
confidence: 99%